Profil Mahasiswa Program Studi Pendidikan Biologi FKIP UMS dalam Melaksanakan Skripsi Tahun 2014 - Susilawati, Yeni Eka, Dra. Hariyatmi, M. Si, Drs. Djumadi, M. Kes (2016)
Research paper is one of form of masterpiece writes is scientific yielded by student as requirement to get college degree. Purpose of this research is to know trends analysis in biology education students of FKIP UMS 2014 in conducting research paper. The method of the research is qualitative descriptive using paper documentation. This reserach is using model survey strategy to obtain and explain the data, as a result the result can describe completely and circumstantial about social reality and various phenomenous.The data analysis tehnique used descriptive qualitative. Based on the results of the study, the selected areas of research students are applied (44,8%), education (28,5%), and pure ( 26,7%). The selected student research approach is quantitative (46,5%), combination (34,3%),as well as the qualitative (19,2%). The research method selected students experiment (85,5%), descriptive (11,0%), class action research (2,9%), dan eksploration (0,6%). Study schools are being focused in educational research, junior high school (73,5%), university (16,3%), senior high school (10,2%), and vocational high school (0%). Thus, can be concluded that the students of Biology Education school of teacher training and education in Muhammadiyah University of Surakarta who graduated in 2014 had a tendency to choose the field af applied research, quantitatve research approach, the eksperimental method, as well as junior high school (73,5%) are being focused in educational research